The histone deacetylase inhibitor CT-101 flips the switch to fetal hemoglobin expression in sickle cell disease mice. - Mayuko Takezaki; Biaoru Li; Hongyan Xu; Nikhil Patel; Rudolf Lucas; Ryan E Cerbone; Sivanagireddy Koti; Clifford L Hendrick; Louis H Junker; Betty S Pace (PLoS ONE)
The most common hemoglobin disorder worldwide is sickle cell disease (SCD) caused by a point mutation in the adult β-globin gene. As a result, hemoglobin S production occurs leading to clinical symptoms including vaso-occlusive pain, organ damage, and a shortened lifespan. Hydroxyurea is the only FDA-approved fetal hemoglobin (HbF) inducer in the United States that ameliorates the clinical severity of SCD. Due to challenges with hydroxyurea, our study aimed to address the unmet need for the development of non-chemotherapeutic HbF inducers. We investigated the ability of CT-101, a Class 1 histone deacetylase inhibitor, to flip the γ-globin to β-globin switch in a humanized SCD mouse model. Pharmacokinetic parameters were assessed in CD-1 and Townes SCD mice after a single intraperitoneal drug dose. Similar drug uptake and half-life were observed in both animals. Subsequent studies in β-YAC mice expressing human γ-globin and β-globin genes established the optimal dose of CT-101 that induces HbF without peripheral blood toxicity. Subsequent confirmatory studies were conducted in the SCD mouse treated with intraperitoneal CT-101, demonstrating increases in F-cells, HbF, and γ-globin gene mRNA levels. Hydroxyurea combined with CT-101 significantly decreased spleen size and hemorrhagic infarcts and improved splenic extramedullary hematopoiesis. Our novel agent, CT-101, flipped the switch by activating γ-globin gene transcription and HbF protein synthesis in the preclinical SCD mouse model without significant toxicity in the peripheral blood. These findings support the development of an oral CT-101 formulation for clinical testing in SCD.